36 HARI PENGEMBANGAN DESA BARU MENJADI DESA BERWAWASAN LINGKUNGAN DAN SEJAHTERA - Christianingrum Christianingrum; Anggraeni Yunita (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2016)
One of the objectives of the Community Service Program (KKN) is the realization of integration and participation of the University's academic community in studying and solving various community problems, fostering and developing religious and social life in rural areas. In their community service activities, students provide experience in science, technology, art, and religion to provide direction in order to solve problems and overcome them appropriately. In addition, improving facilities and infrastructure is one of the activities carried out and becomes a work program for students. In other words, through the activities of the Real Work Lecture (KKN) activities, students can help the development in an area, improve human resources for both students and the community. human resources both for students and for the community in / / processing natural resources and in the community life sector, especially in the field of tourism. So that it is possible for an the area becomes a Tourism Attraction Object (ODTW) that can improve the welfare of the people around it.